Penerapan Black Box Testing pada Website Cobalt.tools untuk Pengujian Fungsionalitas Pengunduhan Media - M. Sunandi; Devan Zulfangga; Dede Ardiansah; Muhammad Rasyid Shiddiq; Siti Rahmah; Subhanjaya Angga Atmaja (Journal on Pustaka Cendekia Informatika, 2025)
This study aims to assess the core functionalities of Cobalt.tools in supporting cross-platform media downloads using the Black Box Testing approach and the Equivalence Partitioning technique. The research employs a descriptive quantitative design, focusing on testing 11 scenarios involving download and configuration features. Each scenario was evaluated based on the alignment between system input and output without examining the internal code structure. Data were collected manually through direct observation and recorded in a test table, then analyzed using quantitative descriptive techniques to measure functional success rates. The results show that all major features of the site operated as expected, with a 100% success rate, confirming the hypothesis regarding the platform’s functional reliability. These findings affirm the effectiveness of Black Box Testing in user interface-based system evaluation. This study contributes to the literature on web-based system testing and offers practical insights for developers seeking to enhance application stability and user experience. Future research is recommended to explore aspects such as security, integration, and system performance on a broader scales.